Separator Wettability Enhanced by Electrolyte Additive to Boost the Electrochemical Performance of Lithium Metal Batteries - Wang, Ying (Nano-Micro Letters, 2021)
Lithium (Li) metal has been regarded as one of the most promising candidates to replace graphite anode due to its high theoretical specific capacity and the lowest electrochemical potential [<a id="ref-link-section-d7539695e272" title="S. Xia, X. Wu, Z. Zhang, Y. Cui, W. Liu, Practical challenges and future perspectives of all-solid-state lithium-metal batteries. Chem 5(4), 753–785 (2019). https://doi.org/10.1016/j.chempr.2018.11.013 " href="https://link.springer.com/article/10.1007/s40820-021-00731-2#ref-CR1" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref">1,<a id="ref-link-section-d7539695e272_1" title="X. Shen, H. Liu, X. Cheng, C. Yan, J. Huang, Beyond lithium ion batteries: higher energy density battery systems based on lithium metal anodes. Energy Stor. Mater. 12, 161–175 (2018). https://doi.org/10.1016/j.ensm.2017.12.002 " href="https://link.springer.com/article/10.1007/s40820-021-00731-2#ref-CR2" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref">2,<a id="ref-link-section-d7539695e275" title="X. Cheng, R. Zhang, C. Zhao, Q. Zhang, Toward safe lithium metal anode in rechargeable batteries: a review. Chem. Rev. 117(15), 10403–10473 (2017). https://doi.org/10.1021/acs.chemrev.7b00115 " href="https://link.springer.com/article/10.1007/s40820-021-00731-2#ref-CR3" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref" aria-label="Reference 3">3]. However, the immoderate growth of Li dendrite during Li plating/stripping causes serious safety problem and poor performance that severely impedes the practical application of lithium metal batteries (LMBs) [<a id="ref-link-section-d7539695e278" title="N. Wu, Y. Li, A. Dolocan, W. Li, H. Xu et al., In situ formation of Li3P layer enables fast Li+ conduction across Li/solid polymer electrolyte interface. Adv. Funct. Mater. 30(22), 2000831 (2020). https://doi.org/10.1002/adfm.202000831 " href="https://link.springer.com/article/10.1007/s40820-021-00731-2#ref-CR4" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref">4,<a id="ref-link-section-d7539695e278_1" title="D. Lin, Y. Liu, Y. Cui, Reviving the lithium metal anode for high-energy batteries. Nat. Nanotechnol. 12, 194–206 (2017). https://doi.org/10.1038/nnano.2017.16 " href="https://link.springer.com/article/10.1007/s40820-021-00731-2#ref-CR5" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref">5,<a id="ref-link-section-d7539695e281" title="S. Bai, X. Liu, K. Zhu, S. Wu, H. Zhou, Metal–organic framework-based separator for lithium–sulfur batteries. Nat. Energy 1, 16094 (2016). https://doi.org/10.1038/nenergy.2016.94 " href="https://link.springer.com/article/10.1007/s40820-021-00731-2#ref-CR6" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref" aria-label="Reference 6">6]. Until now, there have been numerous kinds of strategies be proposed to inhibit Li dendrites growth and protect lithium metal anode such as high concentration electrolytes [<a id="ref-link-section-d7539695e284" title="X. Fan, L. Chen, X. Ji, T. Deng, S. Hou et al., Highly fluorinated interphases enable high-voltage Li-metal batteries. Chem 4(1), 174–185 (2018). https://doi.org/10.1016/j.chempr.2017.10.017 " href="https://link.springer.com/article/10.1007/s40820-021-00731-2#ref-CR7" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref" aria-label="Reference 7">7], construction of the solid electrolyte interface layer [<a id="ref-link-section-d7539695e288" title="F. Li, J. He, J. Liu, M. Wu, Y. Hou et al., Gradient solid electrolyte interphase and lithium-ion solvation regulated by bisfluoroacetamide for stable lithium metal batteries. Angew. Chem. Int. Ed. 60(12), 6600–6608 (2021). https://doi.org/10.1002/anie.202013993 " href="https://link.springer.com/article/10.1007/s40820-021-00731-2#ref-CR8" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref" aria-label="Reference 8">8], structural design of anode materials [<a id="ref-link-section-d7539695e291" title="Y. Feng, C. Zhang, B. Li, B. Li, S. Xiong et al., Low-volume-change, dendrite-free lithium metal anodes enabled by lithophilic 3D matrix with LiF-enriched surface. J. Mater. Chem. A 7(11), 6090–6098 (2019). https://doi.org/10.1039/C8TA10779C " href="https://link.springer.com/article/10.1007/s40820-021-00731-2#ref-CR9" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref" aria-label="Reference 9">9], regulation of Li+ solvation [<a id="ref-link-section-d7539695e296" title="H. Wang, J. He, J. Liu, S. Qi, M. Wu et al., Electrolytes enriched by crown ethers for lithium metal batteries. Adv. Funct. Mater. 31(2), 2002578 (2020). https://doi.org/10.1002/adfm.202002578 " href="https://link.springer.com/article/10.1007/s40820-021-00731-2#ref-CR10" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref" aria-label="Reference 10">10], and solid-state electrolytes [<a id="ref-link-section-d7539695e299" title="T. Famprikis, P. Canepa, J.A. Dawson, M.S. Islam, C. Masquelier, Fundamentals of inorganic solid-state electrolytes for batteries. Nat. Mater. 18, 1278–1291 (2019). https://doi.org/10.1038/s41563-019-0431-3 " href="https://link.springer.com/article/10.1007/s40820-021-00731-2#ref-CR11" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref" aria-label="Reference 11">11]. As an important part of battery structure, separator plays a vital role in the performance of battery [<a id="ref-link-section-d7539695e302" title="M. Ryou, D.J. Lee, J. Lee, Y.M. Lee, J.K. Park et al., Excellent cycle life of lithium-metal anodes in lithium-ion batteries with mussel-inspired polydopamine-coated separators. Adv. Energy Mater. 2(6), 645–650 (2012). https://doi.org/10.1002/aenm.201100687 " href="https://link.springer.com/article/10.1007/s40820-021-00731-2#ref-CR12" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref" aria-label="Reference 12">12]. The main function of separator is to divide the anode and cathode that prevents internal short circuit caused by direct contact between anode and cathode. So, the separator needs to be electrically insulated. At the same time, the separator also needs to ensure that the electrolyte is conductive between anode and cathode [<a id="ref-link-section-d7539695e306" title="H. Zheng, Y. Xie, H. Xiang, P. Shi, X. Liang et al., A bifunctional electrolyte additive for separator wetting and dendrite suppression in lithium metal batteries. Electrochim. Acta 270, 62–69 (2018). https://doi.org/10.1016/j.electacta.2018.03.089 " href="https://link.springer.com/article/10.1007/s40820-021-00731-2#ref-CR13" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref" aria-label="Reference 13">13]. Therefore, it is necessary to render the separator fully wetted. Nevertheless, there are few researches on enhancing the wettability of the separator especially functional electrolyte additives.